Rhizophoraceae Flower and Fruit Morphology as Evidence of Resilience of Mangrove Revegetation in Lembar West Lombok - Ayu Diah Kusumadewi Anak Agung; Agil Al Idrus (Jurnal Biologi Tropis, 2023)
The stability of the mangrove ecosystem is influenced by climate change. One indicator of the resilience of mangrove species is the emergence of reproductive organs (flowers and fruit). The purpose of this study was to describe the morphological characteristics of fruit and flowers as evidence of the resilience of mangrove revegetation in West Lombok. This research was conducted in a mangrove area on the coast of West Lombok. The samples of this study were all species of the Rhizoporaceae family from revegetation. Mangrove data which includes the names of revegetation mangrove species from the Rhizoporaceae family using the transect method. Furthermore, data analysis was carried out qualitatively and quantitatively. Qualitative analysis was conducted to describe the types of mangroves. Quantitative analysis was conducted to explain the diversity of mangrove species. Mangrove diversity can be determined using the diversity theory by Shannon-Wienner (H'). Based on the results of mangrove data which includes the names of revegetated mangrove species from the Rhizophoraceae family, three mangrove species were found, namely Rhizophora mucronate, Rhizophora stylosa, and Rhizophora apiculata which identified the morphological characteristics of the fruit and flowers. The results of this study indicate the results of the diversity index value H'1 < H'< 3, then the diversity index is categorized as medium. So it can be concluded that the morphological characteristics of fruit and flowers in the Rhizophoraceae family can be used as evidence of the resilience of mangrove revegetation results.